Faktor-Faktor yang Mempengaruhi Peralihan Gaya Hidup Punk di Kalangan Remaja di Bukittinggi - Annisa ‘Uliya Rasyida; Yeni Afrida (Lembaga Yasin AlSys, 2026)
Although the phenomenon of the punk lifestyle among adolescents has been widely studied, research specifically analyzing the factors influencing adolescents’ transition to a punk lifestyle in Bukittinggi City remains limited. This study aimed to analyze the internal and external factors influencing the transition to a punk lifestyle among adolescents in Bukittinggi City. The study employed a qualitative approach with a case study design and involved 10 informants selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that the transition to a punk lifestyle was influenced by internal factors, including the search for self-identity, the need for freedom of expression, and the desire to gain social acceptance. External factors included disharmonious family conditions, limited parental attention, peer influence, the social environment, and economic conditions as a supporting factor. These findings confirm that the transition to a punk lifestyle results from the interaction between individual psychological factors and the social environment. This study contributes to the development of Alfred Adler’s style of life theory in explaining adolescent behavior and broadens the understanding of the psychological and social dynamics underlying adolescents’ involvement in punk communities. The implications of this study include theoretical contributions to social psychology and guidance and counseling studies, as well as practical implications for families, schools, and the government in designing adolescent development programs responsive to their psychological and social needs. Future research is recommended to expand the geographical scope and employ a mixed-methods approach. Keywords: Punk Lifestyle; Adolescents; Style of Life; Internal Factors; External Factors